Experimental type: Night meeting: mockup - Smith, Summer (My University, 2021)
This project uses the beginning of the story Night Meeting by Ray Bradbury to explore experimental type. The start of Night Meeting begins with Tomás driving through colonized planet Mars. He chats at a gas station, daydreams about time, and meets a Martian while he stops to rest. When Tomás and the Martian meet, they cannot touch each other and eventually realize that they have met due to a time anomaly. There are many repeating concepts within this first part of the story: feeling different, feeling alone, and time. This spread uses rhythm and colour to explore these repeating motifs. The use of breaks in the text, italics, and different typefaces uses rhythm to highlight when a character feels different or lonely. Colour is used to separate the parts of the story that are explicitly about time. Like time acts differently in the story, the word “time” itself acts differently within the text. The use of breaks within the text highlights the eloquent and poetically written prose. Course: DESN 231 Typography II.
Keywords: typography; layout